STRATEGI MANAJEMEN KONFLIK YANG DITERAPKAN PAULUS DI JEMAAT KORINTUS BERDASARKAN TEKS 1 KORINTUS 3:1-17 - Adi Putra (Phronesis: Jurnal Teologi dan Misi, 2022)
This research focuses on finding Paul's conflict management strategies to resolve conflicts in the Corinthian Church. For this reason, this study analyzes the text of 1 Corinthians 3:1-17. Moreover, by using the exegesis study of the passage above, the researcher found several conflict management strategies that were applied by Paul there. Such as accommodative strategies (Paul gives advice and warnings), avoiding (Paul explains the substance of a servant), collaboration (the Church puts aside the ego and explanations that Paul and Apollos are just servants), and compromise (prioritizes common interests and sees the Church as a building of God that must unite).